A comprehensive review on the synthesis techniques of porous materials for gas separation and catalysis. (12th August 2022) - Sharma, Vikrant; Agrawal, Ankit; Singh, Omvir; Goyal, Reena; Sarkar, Bipul; Gopinathan, Navin; Gumfekar, Sarang P.
Abstract: Intrinsic structural characteristics of porous materials have found significant applications in selective separation of gases and heterogeneous catalysis. While using porous materials for gas separation and catalysis, some of the challenging issues are the strength of catalytic sites, hydrothermal stability, crystalline order of solids, and selectivity. Researchers' ability to engineer the synthesis strategies rationally can help overcome technological challenges. In recent years, breakthroughs in porous materials are focused on developing different chemistries to control the pore architecture. This review focuses on recent advances made in synthesis strategies of porous materials and their impact on gas separation and catalysis applications. A significant part of this review is devoted to various synthesis methods, such as various types of templating methods, molecular layer deposition, sol–gel technique, and polymerization methods. Improvement in various catalytic reactions and gas separations due to different functionalization methods is also summarized. Lastly, we have discussed the applications of porous materials in the form of adsorbents and membranes in commercial processes. We hope that this review will serve as a quick reference for beginners who want to synthesize porous materials with control of pore structure.